2016
DOI: 10.1177/1359105316669584
|View full text |Cite
|
Sign up to set email alerts
|

Maternal responses to difficult food request scenarios: Relationships with feeding style and child unhealthy snack intake

Abstract: This study sought to identify parent-feeding behaviours in real-life difficult feeding situations through the use of a set of scenarios. These were then used to examine links between parent feeding and child snack intake. Mothers of children aged 2-7 years ( n = 611) completed an online survey containing five snack food request scenarios, two commonly used parent-feeding scales (Restriction and Covert Control), and reported on their child's snack intake. Results showed that parent-feeding styles (restrictive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…For example, parents may simply not have unhealthy foods within the home environment and avoid places that serve primarily unhealthy foods when eating out (Ogden, Reynolds & Smith, 2006). A small number of cross-sectional studies have shown that covert feeding strategies are associated with greater healthy snack intake and less unhealthy snack intake in older children aged 9-13 years (Brown et al, 2008;Ogden et al, 2006;Rodenberg et al, 2011) and in younger children aged 2-7 years . To our knowledge, there has only been one longitudinal study of the effects of parental covert control.…”
Section: While Twin Studies Have Shown That Both Genetic and Environmmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, parents may simply not have unhealthy foods within the home environment and avoid places that serve primarily unhealthy foods when eating out (Ogden, Reynolds & Smith, 2006). A small number of cross-sectional studies have shown that covert feeding strategies are associated with greater healthy snack intake and less unhealthy snack intake in older children aged 9-13 years (Brown et al, 2008;Ogden et al, 2006;Rodenberg et al, 2011) and in younger children aged 2-7 years . To our knowledge, there has only been one longitudinal study of the effects of parental covert control.…”
Section: While Twin Studies Have Shown That Both Genetic and Environmmentioning
confidence: 99%
“…One difficulty that needs to be acknowledged is that the use of covert control techniques may require a level of planning and preparation on the part of parents. Hence existing parenting programs could usefully include education about feeding strategies for promoting healthy eating in children, including teaching parents appropriate responses to specific (and often difficult) snack situations that they may face on an everyday basis (Boots et al, 2016). This type of parental feeding strategy may constitute a particular form of proactive parenting, which has been shown to facilitate child learning in other domains (Chang et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Even in young children there will be unavoidable situations such as shopping trips, parties, in which children will haveM A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPTaccess or potential access to snack foods. An investigation of how parents respond in these particular situations and how this affects the child's self-regulation in the future is a worthwhile area of investigation[41].Frequency of Snack Food Consumption, another indicator of amount of snacks the child has access to, did not have the same moderating influence as Allow Access. This result is surprising as the frequency with which snacks are consumed are an indicator of access of snack foods and might be expected to operate in the same way as a moderator.…”
mentioning
confidence: 98%
“…Some parents view snacks as a quick way to “tide a child over” until mealtime (Younginer et al., 2016), for example, whereas others offer children food on a fixed schedule but do not consider this snacking (Jacquier, Gatrell, & Bingley, 2017). Parents seem to use a range of strategies to manage child snack intake (Boots et al., 2016) but in general food parenting outside of mealtimes, particularly as it occurs in naturalistic settings, is not yet fully understood (Davison et al, 2015; Jacquier et al, 2017). Prior work also suggests that family stress arises around managing child needs, specifically hunger, while attempting meal preparation (Norman et al, 2015), and maternal stress due to limited time for meal preparation has frequently been reported (Beshara, Hutchinson, & Wilson, 2010; Devine, Connors, Sobal, & Bisogni, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have observed maternal feeding practices specifically during mealtimes have found positive associations between observed encouraging feeding behaviors, such as food as a reward or praise, and child eating compliance (Haycraft & Blissett, 2008; Orrell-Valente et al, 2007). Naturalistic, observational assessment of parent-child interactions outside of mealtime has been recommended in order to inform prior findings from observational mealtime research, as it is not clear whether food parenting behaviors are similar across all settings (Boots, Tiggemann, & Corsini, 2016; Hughes et al, 2013). …”
Section: Introductionmentioning
confidence: 99%